2015
DOI: 10.1007/s11065-015-9305-x
|View full text |Cite
|
Sign up to set email alerts
|

Aging with HIV-1 Infection: Motor Functions, Cognition, and Attention – A Comparison with Parkinson’s Disease

Abstract: Recent advances in highly active anti-retroviral therapy (HAART) in their various combinations have dramatically increased the life expectancies of HIV-infected persons. People diagnosed with HIV are living beyond the age of 50 but are experiencing the cumulative effects of HIV infection and aging on brain function. In HIV-infected aging individuals, the potential synergy between immunosenescence and HIV viral loads increases susceptibility to HIV-related brain injury and functional brain network degradation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 200 publications
(248 reference statements)
0
28
0
2
Order By: Relevance
“…Other combination and/or regimen are selected based primarily on antiviral efficacy, potential adverse effects (toxicity), pill burden, drug-drug interaction, comorbid conditions and cost (see [124] on 12/1/2016). As a result of effective cART, HIV-1 infection has become a chronic condition and infected individuals have a longer, near normal life span leading to aging with HIV as a new clinical phenomenon [51,127,128,129]. …”
Section: Neurotoxicity Of Antiretroviral Drugsmentioning
confidence: 99%
“…Other combination and/or regimen are selected based primarily on antiviral efficacy, potential adverse effects (toxicity), pill burden, drug-drug interaction, comorbid conditions and cost (see [124] on 12/1/2016). As a result of effective cART, HIV-1 infection has become a chronic condition and infected individuals have a longer, near normal life span leading to aging with HIV as a new clinical phenomenon [51,127,128,129]. …”
Section: Neurotoxicity Of Antiretroviral Drugsmentioning
confidence: 99%
“…A large subset of HIV-infected patients present akinetic Parkinsonian syndromes at the early stage of disease onset, but PD-like syndromes are mostly reversed by HAART depending on the age and genetic predisposition of the patient [227, 228]. Patients who survive beyond 50 years of age most often exhibit accelerated degradation of neural networks compared with age-matched controls, mostly in the basal ganglia and hippocampal regions, due to the synergistic effects of immune-senescence and sustained viral load, despite beingundercontrol[229]. Multiplestudies,inpatients and animal models, show that dopaminergic neurons are the most vulnerable to HIV-infection.…”
Section: Other Neurodegenerative Diseases Linked To Hiv Infectionmentioning
confidence: 99%
“…Multiplestudies,inpatients and animal models, show that dopaminergic neurons are the most vulnerable to HIV-infection. Interestingly, increased levels of α-synuclein are found in the substantia nigra of HIV-infected patients compared with that of normal age-matched controls[229],which is one major cause of the depletion of dopaminergic neurons in α-synuclein gene triplication-associated PD. In a separate study, Riederer and colleagues showed in a primate model that HIV infection can decrease dopamine levels by at least 44% within only 2 months of infection, which is consistent with observations of HIV-infected patients [230].…”
Section: Other Neurodegenerative Diseases Linked To Hiv Infectionmentioning
confidence: 99%
“…Las comorbilidades más frecuentes en esta población son las infecciosas y le siguen las cardiovasculares, metabólicas, neoplasias, osteoporosis y enfermedades neurológicas degenerativas (4,5).…”
Section: Introductionunclassified